2020
DOI: 10.3390/catal10070761
|View full text |Cite
|
Sign up to set email alerts
|

Abatement of Toluene Using a Sequential Adsorption-Catalytic Oxidation Process: Comparative Study of Potential Adsorbent/Catalytic Materials

Abstract: A novel strategy for toluene abatement was investigated using a sequential adsorption-regeneration process. Commercial Hopcalite (CuMn2Ox, Purelyst101MD), Ceria nanorods, and UiO-66-SO3H, a metal–organic framework (MOF), were selected for this study. Toluene was first adsorbed on the material and a mild thermal activation was performed afterwards in order to oxidize toluene into CO2 and H2O. The materials were characterized by XRD, N2 adsorption-desorption analysis, H2-TPR and TGA/DSC. The best dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
(54 reference statements)
4
14
0
Order By: Relevance
“…The increasing amount of adsorbed toluene has been claimed to have negative effects on both the desorption of unconverted toluene and the efficiency of the oxidation process. Some carbon deposits on the inner walls of the plasma reactor and/or adsorbed species remaining on the packed bed material after the in-situ NTP treatment can account for the small carbon deficiency observed in this study, as was already previously reported in literature [24,28] in line with the absence of other gaseous organic species in the outlet of the reactor (observed by FT-IR).…”
Section: Effect Of Toluene Exposure Time On Apc Process Performancessupporting
confidence: 88%
See 3 more Smart Citations
“…The increasing amount of adsorbed toluene has been claimed to have negative effects on both the desorption of unconverted toluene and the efficiency of the oxidation process. Some carbon deposits on the inner walls of the plasma reactor and/or adsorbed species remaining on the packed bed material after the in-situ NTP treatment can account for the small carbon deficiency observed in this study, as was already previously reported in literature [24,28] in line with the absence of other gaseous organic species in the outlet of the reactor (observed by FT-IR).…”
Section: Effect Of Toluene Exposure Time On Apc Process Performancessupporting
confidence: 88%
“…The transient productions reach the first maximum (shoulder) value between 1 and 3 min of plasma exposure and the second maximum value between 7 and 9 min of plasma exposure and return to baseline beyond 20 min of plasma treatment. This type of behavior has been previously observed over Hopcalite whether it is by thermal desorption [24] or NTP exposure [23]. Most of the CO 2 produced in the first minutes of NTP exposure is released in the gas phase and some surface sites are thus liberated.…”
Section: Effect Of Toluene Exposure Time On Apc Process Performancessupporting
confidence: 70%
See 2 more Smart Citations
“…Although these reactor configurations have been proven to be successfully operated, clearly, they give no room for process integration between endothermic desorption and exothermic oxidation and thus can be cost intensive. The third configuration is the one-bed–one-column reactor. In this configuration, adsorption and desorption/catalysis occur sequentially in the same bed. This has the advantages of process integration and thus can be energy and cost efficient.…”
Section: Introductionmentioning
confidence: 99%